Ecological risk assessment of metal and hydrocarbon pollution in sediments from an urban tropical estuary: Tijuca lagoon (Rio de Janeiro, Brazil) - Teixeira, Matheus; Cesar, Ricardo; Abessa, Denis [UNESP]; Siqueira, Celeste; Lourenço, Rodrigo; Vezzone, Mariana; Fernandes, Yan; Koifman, Gustavo; Perina, Fernando Cesar [UNESP]; Anjos, Roberto Meigikos dos; Polivanov, Helena; Castilhos, Zuleica (Springer Nature, 2022)
Urban tropical lagoons are often impacted by eutrophication, metal, and polycyclic aromatic hydrocarbon (PAH) contamination, but the toxicity of their bottom sediments is still poorly investigated in South America. Aiming to contribute to filling this gap, a sediment quality assessment was conducted in the Tijuca Lagoon (Rio de Janeiro, Brazil) using different lines of evidence (LOEs) including sediment characterization, determination of metals and PAHs, and acute toxicity testing with burrowing amphipods (Tiburonella viscana). Mud and organic matter contents played a crucial role in contaminant distribution along the lagoon. The concentrations of PAH were generally low (mean ΣPAH = 795.42 ± 1146.2 ng/g; n = 23), but a contamination hotspot of light PAH compounds was identified. Such PAHs were mainly pyrolytic, probably related to the deposition of atmospheric pollution, although petrogenic compounds also occur in the lagoon. The data indicated the occurrence of geochemical anomalies of Zn, Cu, Pb, and Hg (mean values = 176.9 ± 91.6, 45.1 ± 21.3, 35.2 ± 15.0, 0.1442 ± 0.0893 mg/kg, respectively; n = 23), probably associated with industrial wastes, garbage deposition, urban runoff, and domestic sewage contributions. The mortality of T. viscana was significant for more than 85% of the samples (mean mortality = 70.3 ± 26.0%; n = 23), but it was not significantly correlated with PAH and metal concentrations. On the other side, domestic sewage contributions and eutrophication seem to play a relevant role in sediment toxicity. Actually, the toxicity observed in the tests seems to be due to the simultaneous influence of multiple toxicants and their combined effects on the organisms. Such stressors may include not only metals, PAH, and eutrophication but also chemicals not evaluated in this study, such as hormones, pharmaceuticals and personal care compounds, perfluorocompounds, detergents, and others.
Keywords: Bioassay; Contamination; Sediment quality; Toxicity